MANAJEMEN REDAKSI MEDIA KONTEKS.CO.ID DALAM PENYAJIAN BERITA - Fauziah, Fauziah; Suci, Qur’aini Hamidea (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
The development of technology and the internet has transformed the way information is disseminated, making online media the preferred choice over print media. In Indonesia, with high internet penetration, the use of smartphones for news consumption has surged, driving the growth of digital platforms like Konteks.co.id. This media outlet has thrived due to its effective editorial management strategies, which are crucial for determining the quality and relevance of news and building audience trust.This study employs a qualitative descriptive method to examine the editorial management strategies of Konteks.co.id, focusing on planning, organizing, executing, and controlling processes. The findings reveal that the implementation of the POAC (Planning, Organizing, Acting, Controlling) functions is effective and well-structured. This is evidenced by the rise in Konteks.co.id's ranking among Indonesia's digital media from 2022 to 2024. The planning process involves editorial meetings to decide on topics and scheduling, while execution includes information gathering, verification by reporters, and editing through the CMS. Regular evaluations by the editorial team ensure news quality, and collaboration with the social media